2016
DOI: 10.1542/peds.2015-3087
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Standing Desks and Sedentary Behavior: A Systematic Review

Abstract: CONTEXT: Reducing sedentary behaviors, or time spent sitting, is an important target for health promotion in children. Standing desks in schools may be a feasible, modifiable, and acceptable environmental strategy to this end. OBJECTIVE:To examine the impact of school-based standing desk interventions on sedentary behavior and physical activity, health-related outcomes, and academic and behavioral outcomes in school-aged children.DATA SOURCES: Ovid Embase, Medline, PsycINFO, Web of Science, Global Health, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 49 publications
7
94
0
1
Order By: Relevance
“…A recent review that explored the impact of standing desks on sedentary time and physical activity time in children found inconsistent results for school time effects [30]. Some studies found that stepping time and total step count did not increase with the use of standing desks when compared to baseline measurements or the control group [32,43,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review that explored the impact of standing desks on sedentary time and physical activity time in children found inconsistent results for school time effects [30]. Some studies found that stepping time and total step count did not increase with the use of standing desks when compared to baseline measurements or the control group [32,43,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the study indicated that the students who utilized the standing desks had a significant increase in energy expenditure compared to the control group who did not utilize the stand-biased desks. Minges et al (2016) completed a systematic review of eight studies that examined the effect of standing desks on children's physical activity levels, sit and stand behaviors, classroom behaviors, and academic performance. Results suggested that time standing increased in all studies, time spent sitting decreased in all studies, and physical activity and positive academic behavior increased in most studies.…”
Section: Forms Of Alternative Seating Standing Desksmentioning
confidence: 99%
“…In this sense, even if a large part of current interventions aimed at reducing and/or disrupting adolescent sedentary behavior are school-based, such as the use of height adjustment tables 25 , these findings lead to the recommendation that future interventions should also emphasize the period outside school, such as the use of measures to reduce screen time or even family interventions 26 . The high sample loss, due to a low rate of individuals with valid accelerometer data (57%), is one of the main limiting factors of the study.…”
Section: Discussionmentioning
confidence: 99%